The effect of Cognitive Behavioral Couples Therapy (CBCT) in marital: a literature review - Othman, Mohd Hatta; Mohd Rifin, Mohd Hadri; Hassan, Hazaila (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2025)
Cognitive Behavioral Couple Therapy (CBCT) relies on the principles of social learning theory and focuses on the interaction between cognition, behavior, and emotional responses of couples to help improve their communication and problem-solving. This study identifies the research design and sample related to the effects of CBCT, data collection methods, the questionnaire on the effects of CBCT and the themes of the effects of CBCT. This study uses a meta-synthesis design and has systematically analyzed 25 articles from 1996 to 2024. The findings for the first objective show that all articles used quantitative research with experimental designs, nine studies used true experiment, 13 studies used quasi-experiment and only three studies used semi-experiment designs. The overall sample size of the studies shows that 15 studies involved 517 couples and 10 studies involved 484 individuals. The findings for the second objective indicate that all studies are survey study with questionnaire methods. Meanwhile, the findings of the third objective revealed five identified themes mental health, sexuality, conflict, stress, and quality of marital. This article is also recommended for further studies related to the effects of CBCT in Malaysia.